TERAPI RELAKSASI AKUPRESUR UNTUK MENGATASI KELUHAN MUAL DAN MUNTAH PADA IBU HAMIL - Ayu Mayasari, Dyah; Savitri, Wenny (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Nausea and vomiting are the most common symptoms in pregnancy and have affected 50-80% pregnant women. Acupressure is a science of healing by tapping, massaging, and massage the body with the intention of reactivating the energy balance in mother's body because the body adapt  to the changes that occur during pregnancy. With acupressure, especially at point pericardium 6 the balance in the body of mother can be overcome. Objective: To know the effectiveness of acupressure relaxation therapy to reducing complaints of nausea and vomiting in the first trimester pregnancy. Method: This was a quasi experimental study with Case Control design. Sample size was 22 respondents from Rachmi Maternity Hospital Yogyakarta with purposive sampling technique. Data analysis used univariable analysis and bivariable with Mann W hitney U test with a significance level of p<0.05. Results: There was a significant difference in the frequency  of  nausea  and vomiting between  treatment and control groups. The decreased of frequency of nausea and vomiting in the treated group was higher than the control group (p =0.026). Conclusion: Acupressure therapy  i s effective  in  reducing  t h e  complaints  of  nausea and vomiting in first trimester pregnancy at Rachmi Maternity Hospital Yogyakarta. Provide acupressure therapy to pregnant women who complained of nausea and vomiting in trimester I. Create a regular schedule acupressure therapy. Measure the levels of HCG, the hormone endorphin, intestinal peristalsis, the intensity and duration of nausea and vomiting. Keywords : Acupressure, nausea vomiting, pregnancy